Safety and efficacy of l‐threonine produced using Escherichia coliCGMCC 13325 as a feed additive for all animal species. (18th December 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐threonine produced by fermentation when used as a nutritional additive in feed and water for drinking for all animal species and categories. The product under assessment is l ‐threonine produced using a genetically modified strain of E. coli CGMCC 13325. The Panel notes that three out of five batches of the additive do not comply with the minimum specification of 98.5% l ‐threonine on a dry matter basis proposed by the applicant. The production strain and its DNA were not detected in the final additive. Therefore, the final product does not give raise to any safety concern regarding the genetic modification of the production strain. The use of l ‐threonine produced using E. coli CGMCC 13325 in supplementing feed to compensate for threonine deficiency in feedingstuffs is safe for the target species. The FEEDAP Panel identified risks of nutritional imbalances and hygienic concerns for amino acids when administered simultaneously in feed and in water for drinking. The use of l ‐threonine produced by fermentation using E. coli CGMCC 13325 in animal nutrition is considered safe for the consumers and for the environment. There is a risk from the inhalation exposure to endotoxins for persons handling the additive. In the absence of data, the FEEDAP Panel cannot conclude on the potential of l ‐threonine produced using E. coli CGMCC 13325 to be a skin or eye irritant or a skin sensitiser. The additive under assessment is regarded as an effective source of the amino acid l ‐threonine for all non‐ruminant species. For the supplemental l ‐threonine to be as efficacious in ruminants as in non‐ruminant species, it requires protection against degradation in the rumen.